A new damsel-dragonfly of the small family Selenothemistidae from the Late Jurassic of China (Odonata, Isophlebioptera). (20th June 2018) - Huang, Diying; Cai, Chenyang; Nel, André
Abstract: Sinothemis difficilis new genus new species, youngest and first accurate Chinese representative of the small family Selenothemistidae, is described and illustrated. It is closely related to the genus Turanothemis, known from the Karatau outcrop in Kazakhstan. The genus Caraphlebia, known from the Middle Jurassic of Antarctica, seems to strongly differ from the other representatives of this family and may belong to another family. The fossil was collected from the Upper Jurassic (157.3 ± 1.5 Ma; near Oxfordian/Kimmeridgian boundary) Guancaishan locality, Jianping County, Western Liaoning, NE China. It belongs to the late assemblage of the Yanliao biota, while the early assemblage is represented by the putatively close damsel-dragonfly Paraliassophlebia from the Jiulongshan Formation of northern Hebei Province. UUID:http://zoobank.org/8b11b148-852e-4079-a9fb-1884bf4b6d94